The influence of a physical activity program on the body and the cardio vascular parameters of premenopausal women - Ramírez Balas, Almudena; Muñoz Marín, Diego; Timón Andrada, Rafael; Olcina Camacho, Guillermo J.; Robles Gil, Mª Concepción; Maynar Mariño, Marcos (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2012)
During the life cycle of a woman's body figure is changed gradually, but on reaching middle age, as a result of follicular loss of ovarian function among others, are emphasized the physiological changes and increase health risk and welfare. Androgyny in association with obesity increases the risk for diabetes, hypertension, dyslipidemia, atherosclerosis, cardiovascular disease, gallstones, osteoarthritis, arthritis, cancers and other disorders of female middle age. Physical activity has gained importance increasing in therapy in the climacteric. It has demonstrated the positive effects of exercise on cardiovascular disease and weight maintenance. This study investigates the influence of a physical activity program for five months on cardiovascular risk factors like high blood pressure and body composition in premenopausal women. The study included 20 premenopausal women, separated into two groups: younger than 35 years (n = 10), and over 35 years (n = 10). The experimental subjects underwent an assessment of blood pressure and body composition before and after an aerobic training. Results indicate greater extent in reducing diastolic blood pressure and body fat in over 35 years premenopausal women. Therefore, performing aerobics, step and toning improves factors cardiovascular risk as high blood pressure and body composition in over 35 premenopausal women.